A SURVEY OF HARDWARE WATERMARKING FOR PROGRAMMABLE LOGIC DEVICES PROTECTION - V. V. Sergeichik; A. A. Ivaniuk (Informatika)
Application of watermarking technology for the protection of digital devices and their descriptionsis considered. Primary definitions, models, categories of attacks, characteristics and classificationof watermarks are described. Hardware watermarking examples are shown.